The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000019134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic surgery and Lichtenstein repair for treatment of inguinal hernias

Abstract: Background: This study aimed to identify the best procedure for addressing inguinal hernias by comparing results after transabdominal preperitoneal (TAPP), totally extraperitoneal (TEP), and Lichtenstein repairs using a network meta-analysis. Methods: We conducted a systematic search of MEDLINE, Web of Science, the Cochrane Central Library, and ClinicalTrials.gov up to September 1, 2018 for randomized controlled trials (RCTs) comparing the TAPP, TEP, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 60 publications
1
26
0
4
Order By: Relevance
“…В то же время несколько крупных обзоров показали, что лапароскопическая герниопластика ПГ снижает риск формирования острой и хронической послеопе-рационной боли и сокращает время нетрудоспособности пациентов [51,52]. В 2019 г. опубликовано исследование регистра 15-летнего наблюдения за 57 906 пациентами, которым выполнялась пластика Лихтенштейна или лапароскопическая герниопластика (TEP, totally extraperitoneal или TAPP, transabdominal preperitoneal).…”
Section: Surgery хирургияunclassified
“…В то же время несколько крупных обзоров показали, что лапароскопическая герниопластика ПГ снижает риск формирования острой и хронической послеопе-рационной боли и сокращает время нетрудоспособности пациентов [51,52]. В 2019 г. опубликовано исследование регистра 15-летнего наблюдения за 57 906 пациентами, которым выполнялась пластика Лихтенштейна или лапароскопическая герниопластика (TEP, totally extraperitoneal или TAPP, transabdominal preperitoneal).…”
Section: Surgery хирургияunclassified
“…The results of the literature search are presented in Table 1. Seventeen randomised control trials (RCTs) and 11 systematic reviews (SRs) met the inclusion criteria and were included in the analysis 7,12,17–43 . The review revealed two key areas of discussion including the operative method and type of mesh used.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies evaluated the rates of peri‐operative complication between laparoscopic and open‐mesh hernia repairs, including haematoma, seroma, post‐operative pain, wound infection and hydrocele. 18,22–25,27,28,30,31,34,36,38 . Rates of these complications ranged from 2%–8% for haematoma, 5%–13% for seroma and 0%–1% for wound infection across all operative methods 27,44 Four studies reported no difference between open and laparoscopic methods whilst seven documented increased acute post‐operative pain after open repair 18,22–25,27,28,30,31,34,36,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Además, diferentes estudios han demostrado que el abordaje endoscópico es costo/efectivo, y proporciona una recuperación/reincorporación a actividades cotidianas más rápida, así como una menor incidencia de dolor posoperatorio crónico. (3,(13)(14)(15) Por otro lado, las técnicas endoscópicas (TEP y TAPP) tienen ventajas y desventajas propias, por ejemplo, en el TAPP es mas fácil identificar la anatomía, se reducen las probabilidades de lesión vascular, y es preferible en las hernias bilaterales, pero como contraparte, las lesiones intraabdominales son más frecuentes y es necesario cerrar el peritoneo parietal, lo cual puede ser un tiempo laborioso. (3) Hasta ahora la literatura ha fallado en demostrar una clara superioridad de un abordaje endoscópico sobre otro, siendo inconsistentes los estudios comparativos sobre ambas técnicas en cuanto a tiempo operatorio, complicaciones, y recurrencias.…”
Section: Resultsunclassified
“…Estos últimos se estiman entre 2-5% luego del abordaje tipo TAPP, siendo una de las principales ventajas de esta técnica sobre el procedimiento de Lichtenstein. (3,(13)(14)(15) En nuestra serie la presencia de dolor crónico fue del 3,7%, sin casos severos o debilitantes, cediendo paulatinamente en todos los pacientes mediante la administración de analgésicos comunes.…”
Section: Resultsunclassified